Endoscopic ultrasound-guided rendezvous in benign biliary or pancreatic disorders with a 22-gauge needle and a 0.018-inch guidewire - Belén Martínez; Juan Martínez; Juan Antonio Casellas; José R. Aparicio (Endoscopy International Open, 2019)
Background and study aims The aim of this study was to assess the efficacy and safety of endoscopic ultrasound-guided rendezvous (EUS-RV) for benign biliary or pancreatic disorders with a 22-gauge needle and a 0.018-inch guidewire. Patients and methods Patients who underwent EUS-RV after failed biliary or pancreatic cannulation for benign disorder were candidates for this study. For EUS-RV, a 22-gauge needle and a 0.018-inch guidewire were used. Inclusion criteria were unsuccessful biliary or pancreatic cannulation for therapeutic endoscopic retrograde cholangiopancreatography (ERCP) with benign biliary or pancreatic obstruction. Exclusion criteria included malignant biliary or pancreatic obstruction, inaccessible papilla due to surgically altered upper gastrointestinal anatomy or duodenal stricture, and previous sphincterotomy and/or biliary stent placement. The primary outcome was the technical success rate of biliary or pancreatic cannulation, and the secondary outcome was the rate of adverse events. Results Thirty-one patients were evaluated. The overall technical success rate was 80.6 % (81.5 % in biliary and 75 % in pancreatic cases). Adverse events (AEs) were identified in 12.9 % of patients, including one with biliary peritonitis, one with abdominal pain and one with severe pancreatitis plus pneumomediastinum. Only one of the AEs (3.3 %) was directly related to the rendezvous procedure. Conclusions EUS-RV may be a safe and feasible salvage method for unsuccessful cannulation for benign disorders. Use of a 22-gauge needle with a 0.018-inch guidewire may be the first option for benign pathology.